The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/coatings12121864
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Properties of Zinc Oxide Nanoparticles on Candida albicans

Abstract: This paper reports the antifungal properties of zinc oxide nanoparticles (ZnO NPs) on Candida albicans ATCC 1023 through the study of growth inhibitory effects of ZnO NPs on C. albicans and the effect of the nanoparticles on the surface of C. albicans. The growth inhibitory effects of ZnO NPs (5, 10, 20, 40, 80, and 160 µg/mL) on C. albicans at 24 h were determined through the reduction in suspension turbidity and colony count. Fourier transform infrared (FTIR) analysis was carried out to establish the functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 56 publications
2
11
0
Order By: Relevance
“…On the other hand, no activity was shown by CuCl 2 alone and its presence did not significantly affect the WT activity, although Cu 2+ can form stable complexes with calcitermin even at pH 5.4. Of note, previous studies showed that both Zn 2+ and Cu 2+ ions possess antifungal activity per se at concentrations consistent with those used in our study, showing similar minimal inhibitory concentrations, although Zn 2+ was generally proven to be more effective compared to Cu 2+ 29 31 . Our results confirmed the Zn 2+ anti- C. albicans activity, whereas a marked antifungal activity by Cu 2+ ion was not evidenced.…”
Section: Resultssupporting
confidence: 86%
“…On the other hand, no activity was shown by CuCl 2 alone and its presence did not significantly affect the WT activity, although Cu 2+ can form stable complexes with calcitermin even at pH 5.4. Of note, previous studies showed that both Zn 2+ and Cu 2+ ions possess antifungal activity per se at concentrations consistent with those used in our study, showing similar minimal inhibitory concentrations, although Zn 2+ was generally proven to be more effective compared to Cu 2+ 29 31 . Our results confirmed the Zn 2+ anti- C. albicans activity, whereas a marked antifungal activity by Cu 2+ ion was not evidenced.…”
Section: Resultssupporting
confidence: 86%
“…The tests were conducted in triplicate. The zone of inhibition of different doses of ZnO‐NPs was measured and recorded [27,28] …”
Section: Methodsmentioning
confidence: 99%
“…The prime possibility is due to the surface interaction of the zinc oxide nanoparticle with the fungal cell wall. FTIR analysis was used to point out the functional groups that were responsible for these interactions, which indicates the possible interaction of alcohol, amide, methyl, alkynes, and phosphate groups, present on the surface of the nanoparticle, with the yeast cell wall . The above listed interactions lead to the accumulation of the nanoparticle on the cell membrane that further leads to membrane disruption .…”
Section: Resultsmentioning
confidence: 99%
“…FTIR analysis was used to point out the functional groups that were responsible for these interactions, which indicates the possible interaction of alcohol, amide, methyl, alkynes, and phosphate groups, present on the surface of the nanoparticle, with the yeast cell wall. 45 The above listed interactions lead to the accumulation of the nanoparticle on the cell membrane that further leads to membrane disruption. 46 It is also suggested that the exposure to zinc oxide nanoparticles alters the cell structure like—breakage of hyphae, pitting of the cell wall, invagination of the surface, and cell membrane rupture.…”
Section: Resultsmentioning
confidence: 99%